Sinonasal undifferentiated carcinoma: Institutional trend toward induction chemotherapy followed by definitive chemoradiation. Issue 11 (18th July 2020) - London, Nyall R.; Mohyeldin, Ahmed; Daoud, Georges; Gamez, Mauricio E.; Blakaj, Dukagjin; Bonomi, Marcelo; Prevedello, Daniel M.; Carrau, Ricardo L.
Abstract: Background: Recent reports have investigated the nascent role of induction chemotherapy for sinonasal undifferentiated carcinoma (SNUC). The goal of this study was to ascertain trends in treatment pattern changes for SNUC at a single institution and design a treatment algorithm utilized at our institution. Methods: Retrospective chart analysis of 21 cases of SNUC from 2010 to 2018. Results: Of 21 patients in this cohort, 18 (85.7%) presented with T4 disease, 7 (33.3%) presented with nodal disease, and 3 (14.3%) presented with distant metastasis. Since 2016, patients have been managed by induction chemotherapy followed by concurrent chemoradiation. To this point, patients treated with TPF induction chemotherapy followed by concurrent chemoradiation show no evidence of disease; however, the average follow up time is 16.8 months. Conclusions: The multimodality treatment for SNUC continues to evolve, as highlighted by this study, toward increased use of induction chemotherapy followed by chemoradiotherapy.